Overexpression of Modified CENH3 in Maize Stock6-Derived Inducer Lines Can Effectively Improve Maternal Haploid Induction Rates - Meng, Dexuan; Luo, Haishan; Dong, Zhaobin; Huang, Wei; Liu, Fang; Li, Fenghai; Chen, Shaojiang; Yu, Haiqiu; Jin, Weiwei (Frontiers in Plant Science, 2022)
Maize (Zea mays) doubled haploid (DH) breeding is a technology that can efficiently generate inbred lines with homozygous genetic backgrounds. Haploids are usually produced through in vivo induction by haploid inducer lines in maize. Currently, two approaches are usually used to develop maize haploid inducer lines. One is through the conventional breeding improvement based on the Stock6 germplasm, and this strategy is extensively used to induce maternal haploids in commercial maize DH breeding. Another strategy, newly developed but less utilized so far, is by genetic manipulation of the Centromeric Histone3 (CENH3) in regular lines. However, whether both approaches can be combined to develop the haploid inducer line with higher maternal haploid induction rate (HIR) has not been reported. In this study, we manipulated the Stock6-derived inducer lines by overexpressing maize CENH3 fused with different fluorescent protein tags and found that the engineered Stock6-derived lines showed an obvious increase in the maternal HIR. Intriguingly, this above strategy could be further improved by substituting a tail-altered CENH3 for the full-length CENH3 in the tagged expression cassette, resulting in a maternal HIR up to 16.3% that was increased by ~6.1% than Stock6-derived lines control. These results suggested that integration of two in vivo haploid induction methods could rapidly and effectively improve the maternal HIRs of maize Stock6-derived inducer lines, and provided a potentially feasible solution for further optimizing the process of commercial maize DH breeding.